PENGUATAN KEMAMPUAN PROBLEM SOLVING MAHASISWA MELALUI MODEL REAPS - Yulis Jamiah; Revi Lestari Pasaribu (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2023)
Model REAPS dalam pembelajaran memberikan dampak, diantaranya: mengendalikan emosi yang positif dan mengembangkan keterampilan intrapersonal positif. Dampaknya dapat menguatkan kemampuan problem solving melalui interaksi sosial atau kolaborasi yg berupa diskusi antar mahasiswa untuk membahas penyelesaian persoalan. Penelitian ini bertujuan untuk memperoleh gambaran kemampuan problem solving mahasiswa Prodi Pendidikan Matematika FKIP Untan yang mengambil kuliah Program Linier. Tujuan tersebut dicapai melalui beberapa tahap, meliputi: 1) menganalisis teori tentang model REAPS dan karakteristik kemampuan problem solving; 2) mengkaji perangkat pembelajaran, seperti merevisi bahan ajar, rancangan pembelajaran; 3) menyusun instrumen penelitian berupa: tes kemampuan problem solving, lembar observasi, kisi-kisi angket dan angket; 4) memvalidasi instumen penelitian; 4) menerapkan model REAPS; 5) memberikan tes kemampuan problem solving dan angket; 6) menganlisis data hasil penelitian. Metode penelitian yang digunakan adalah Peneltian Tindakan Kelas. Penyaringan dan pengumpulan data dilakukan dengan berbagai cara, baik dengan maupun tanpa pengujian: Pemeriksaan, dokumentasi, observasi dan angket. Teknik analisis data kualitatif dan kuantitatif. Hasil penelitian ini menunjukkan kategori baik. AbstractThe actual Engagement In the lively problem-solving (REAPS) version of getting to know has an impact, including controlling fantastic feelings and growing tremendous intrapersonal talents. The effect can beef up trouble-solving abilities through social interaction or collaboration through discussions between college students about problem-solving. This looks at objectives to reap an outline of the trouble-solving skills of students of the arithmetic training study application, FKIP Untan, in particular, students who take Linear Programming courses. This goal turned into performed via several ranges, including 1) studying the concept of the REAPS model and the traits of hassle-solving capabilities; 2) reviewing getting to know the equipment, along with revising coaching substances and gaining knowledge of designs; three) compiling research gadgets in the shape of trouble-fixing ability tests, statement sheets, questionnaires, and questionnaires; 4) validating research devices; 4) observing the REAPS version; five) giving assessments of trouble-solving talents and questionnaires; 6) studying studies records. The research method used is lecture room movement research. Screening and facts collection has been achieved in diverse approaches, each assessment and non-checks through written exams, documentation, statement, and questionnaires. Qualitative and quantitative records evaluation techniques complement every difference. The outcomes of this study indicate an excellent class.